Dematerialisation of a photographic collection at the concrete institute’s information centre - Shipalana, Kizzy (Library and Information Studies Centre (LISC), 2019)
The Concrete Institute’s information centre houses special collections and information about concrete and various aspects of concrete technology, including photographs that need to be managed effectively for retrieval purposes. The photographic collection has to be recorded and preserved according to relevant standards to ensure longevity and long term access. Management of photographic collections comes with its unique problems. The purpose of this study is to improve the state of the photographic collection by organising it for easy retrieval, allocating metadata and preserving it for future use. This study employed the action research method to study problems of the photographic collection at the institute. The action research method aims to find solutions to problems that are experienced by people in their everyday lives. Data was collected from a sample drawn using purposive sampling from the target population of information specialists and professionals. Data collection from information professionals was facilitated through an online questionnaire and three information specialists were interviewed. The study has indicated the importance of dematerialisation and allocating metadata to photographs to help identify and enhance accessibility of information resources. The results show that dematerialising the photographs will ease the retrieval process and assist information professionals to gain a greater insight of the material in their collection. Collections that are easily accessible are usable and fulfil their purpose to information users. In conclusion, a summarised overview of the study is presented in findings and recommendations regarding the management of photographic collections for effective retrieval.